Influence of Different Functional Elements of Plasmid pGT232 on Maintenance of Recombinant Plasmids in Lactobacillus reuteri Populations In Vitro and In Vivo - Heng, Nicholas C. K. (American Society for Microbiology, 1999)
Plasmid pGT232 (5.1 kb), an indigenous plasmid of Lactobacillus reuteri 100-23, was determined, on the basis of nucleotide and deduced protein sequence data, to belong to the pC194-pUB110 family of plasmids that replicate via the rolling-circle mechanism. The minimal replicon of pGT232 was located on a 1.7-kb sequence consisting of a double-strand origin of replication and a gene encoding the replication initiation protein, repA. An erythromycin-selectable recombinant plasmid containing this minimal replicon was stably maintained (>97% erythromycin-resistant cells) without antibiotic selection in an L. reuteri population under laboratory growth conditions but was poorly maintained (<33% resistant cells) in the L. reuteri population inhabiting the murine gastrointestinal tract. Stable maintenance (>90% resistant cells) of pGT232-derived plasmids in the lactobacillus population in vivo required an additional 1.0-kb sequence which contained a putative single-strand replication origin (SSO). The SSO of pGT232 is believed to be novel and functions in an orientation-specific manner.